IMPROVING THE REPRODUCTIVE PERFORMANCE OF SNAKEHEAD FEMALE BROODSTOCK (Channa striata) USING A COMBINATION OF DIET WITH SUPPLEMENT PROBIOTIC EM4 (EFFECTIVE MICROORGANISM-4) AND NONI FRUIT (Morinda citrifolia) - Telaumbanua, Tuti Feberiani; Djauhari, Ricky; Yusuf, Noor Syarifuddin (Jurnal Perikanan Unram, 2025)
ABSTRACT One of the main limiting factors in the reproduction of snakehead fish (Channa striata) is that the female broodstock fails to spawn, because they cannot complete the final stages of vitellogenesis and ovulation naturally. Therefore, a breakthrough is needed in snakehead fish hatchery to increase the percentage of female broodstock successfully spawning. The aim of this study was to evaluate the effect of providing fermented products combined with probiotic EM4 (Effective Microorganism-4) and noni fruit in feed on the reproductive performance of female broodstock snakehead fish. This research uses non-factorial experimental methods. The design used was a Completely Randomized Design (CRD) with three treatments and three replications, namely treatment A (feed without supplementation of the fermented product with a combination of EM4 probiotics and noni fruit), treatment B (feed with supplementation of the fermented product with a combination of EM4 probiotics and noni fruit at a dose 10%), and treatment C (feed supplemented with fermented products combined with EM4 probiotics and noni fruit at a dose 20%). The results of the research showed that the addition of snakehead female broodstock feed with a fermented product combining EM4 probiotics and noni fruit at a dose of 10% gave the best results, namely an average gonad maturity index (IKG) value of 2.56%, relative fecundity of 3562 eggs per female broodstock, fertilization rate 87.33%, hatching rate 91.67%, and egg yolk absorption time 78 hours, and prolarva survival rate 98.67%. Keywords: female broodstock of Channa striata, noni fruit, reproduction performance, probiotic EM4.